PSYCHOPEDAGOGIC RESOURCES FOR THE DEVELOPMENT OF CHILDREN AND ADOLESCENTS WITH ADHD - Almeida, Flávia da Silva; Coutinho, Diogenes José Gusmão (Revista Ibero-Americana de Humanidades, Ciências e Educação, 2023)
Attention Deficit Hyperactivity Disorder is a developmental disorder whose symptoms cause difficulties in personal and interpersonal life. In children, adolescents and adults, it compromises their functional life with direct consequences in the school context, causing learning problems. In addition to genetic factors, biological and social traits are correlated with the development of the disorder, they fail to meet deadlines, they forget important commitments, such as paying bills commemorative and dates. This article reviews the main psychopedagogical resources aimed at behavior modification, based on Cognitive Behavioral Therapy, and which provide therapeutic work with patients with ADHD. These techniques aim to equip the patient to face conflicts, developing some important functions such as: attention, planning and problem solving, directly related to executive functions, which are precarious in patients with attention deficits. There is evidence in the specialized literature that the application of these techniques suggests gains in the development of executive functions.